2013
DOI: 10.1103/physrevx.3.041002
|View full text |Cite
|
Sign up to set email alerts
|

Stretching Polymers in Droplet-Pinch-Off Experiments

Abstract: Droplet pinch off, which occurs when a drop of liquid detaches from a capillary, can be strongly modified in the presence of polymers, giving rise to long and slender filaments that thin slowly in time. However, little is known experimentally about the molecular conformations of the polymers in the filament itself. Since the thinning dynamics of these filaments can be used to extract macroscopic quantities of interest such as the elongational viscosity of polymer solutions, which is of importance in a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Channels with hyperbolic constrictions can also be designed to minimize shear effects; pressure drop measurements across the constriction, corrected for shear contributions, then provide a direct measure of the extensional viscosity ( Figure ). Other microfluidic designs use the breakup of aqueous droplets in an oil sheath fluid; the extensional viscosity of the polymer solution can then be obtained from the filament thinning dynamics . Intriguingly, such microfluidic experiments have revealed that for sufficient extension rates, the extensional viscosity can abruptly increase—similar to transport measurements on bulk porous media—suggesting a potential contribution to the increased macroscopic flow resistance.…”
Section: Steady Flow Properties Of Bulk Polymer Solutionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Channels with hyperbolic constrictions can also be designed to minimize shear effects; pressure drop measurements across the constriction, corrected for shear contributions, then provide a direct measure of the extensional viscosity ( Figure ). Other microfluidic designs use the breakup of aqueous droplets in an oil sheath fluid; the extensional viscosity of the polymer solution can then be obtained from the filament thinning dynamics . Intriguingly, such microfluidic experiments have revealed that for sufficient extension rates, the extensional viscosity can abruptly increase—similar to transport measurements on bulk porous media—suggesting a potential contribution to the increased macroscopic flow resistance.…”
Section: Steady Flow Properties Of Bulk Polymer Solutionsmentioning
confidence: 95%
“…Hence, the extensional viscosity η e only quantifies the elongation contribution to fluid stress when averaged over sufficiently large spatial and temporal scales. Recent work has also demonstrated the strong role of polymer elongation on the breakup dynamics of aqueous droplets, indicating that such transient extension likely plays an important role in flows involving fluid interfaces, as in EOR and groundwater remediation . While these transient effects are typically neglected in models of polymer solution flow through porous media, ongoing work leveraging microfluidics is beginning to shed light on the central influence of unsteady flows in determining macroscopic transport properties.…”
Section: Steady Flow Of Polymer Solutions In Porous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, drop formation in non-Newtonian fluids, which is important in areas such as emulsification, inkjet printing, and agricultural spraying, is still ill understood in many cases [1][2][3][4] and continues to attract considerable attention [5][6][7][8][9][10][11][12][13]. For instance, theoretical analysis predicts that the drop breakup in shear thinning fluids proceeds faster than that in the Newtonian case due to the high elongational rates present in the fluid neck during the thinning [14,15].…”
Section: Drop Formation In Shear-thickening Granular Suspensionsmentioning
confidence: 99%
“…We follow a simple and direct method to probe the extensional properties of a variety of yield stress fluids by following the capillary thinning dynamics of a fluid neck until it breaks up [5][6][7]. We find that, contrary to expectations, the thinning dynamics shows a nonuniversal behavior that leads to fluid viscosities that depend on the imposed initial deformation.…”
mentioning
confidence: 99%